Impact of Agricultural Practices on Nitrate Pollution in Groundwater in India - Kiara, Shristi (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to examine impact of agricultural practices on nitrate pollution in groundwater in India Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: a significant environmental concern with far-reaching implications for human health, ecosystem integrity, and water resource management. It is evident that agricultural activities such as fertilizer application, irrigation methods, and land management practices play a pivotal role in exacerbating nitrate contamination of groundwater. The studies highlighted the complex interactions between agricultural activities and hydrological processes, elucidating the pathways through which nitrates migrate from soil to groundwater. Unique Contribution to Theory, Practice and Policy: Diffuse Pollution Theory, Hydrological Connectivity Theory & Sustainable Agriculture Theory may be used to anchor future studies on impact of agricultural practices on nitrate pollution in groundwater in India. Encourage the adoption of sustainable agricultural practices that minimize nitrate pollution while maintaining agricultural productivity. This includes promoting precision agriculture techniques, cover cropping, and integrated nutrient management systems to optimize fertilizer use and reduce nitrate leaching. Strengthen regulations and enforcement mechanisms to limit nitrate pollution from agricultural activities. This may include setting stringent water quality standards for nitrate concentrations in groundwater and implementing monitoring programs to assess compliance.